Strategi Implementasi Kebijakan Penyelenggaraan Konservasi Air Tanah Di Kota Bandung - Safta Harmila; Noorsyamsya Djumara; Arundina Dijah Retno Pratiwi (Jurnal Media Administrasi Terapan, 2021)
Ground water should not be used for various purposes, because if it is excessively used it will disturb the balance of the groundwater environment. Various negative impacts of groundwater exploitation include a decrease in groundwater quality, a decrease in the ground water level or land subsidence and the number of unlicensed wells so that groundwater must be managed in balance through conservation. The mandate of the West Java Provincial Regulation Number 1 of 2017 in article 5 (five) that conservation is included in the implementation stage of groundwater management and the mandate of the Bandung City Regional Regulation Number 18 of 2011 which contains control of groundwater use. It is known that groundwater conservation in the city of Bandung has not been implemented properly by groundwater users. As a result, in several areas in the city of Bandung there has been a decrease in the depth of the groundwater level. This occurs because the implementation of policies on the dimensions of communication, resources, disposition, and bureaucratic structure is still not understood as revealed in George C Edwards's theory. Therefore, it is necessary to identify the implementation of groundwater conservation policies in the city of Bandung, namely by analyzing the internal and external environment with the SWOT analysis method of strengths, weaknesses, opportunities and threats and formulating a strategy for implementing the implementation policies. groundwater conservation in the city of Bandung. The results of this strategy formulation can be applied through a program of activities at the Bandung City Government, namely organizing socialization and public awareness through publications, optimizing the manufacture of infiltration wells, biopores, injection wells to control groundwater pollution and analyzing groundwater balance to monitor the decline in groundwater levels.